Представление о справедливости в теории и обыденно-практическом сознании - Лаврухина, Ирина Михайловна; Глушко, Ирина Васильевна; Дикунова, Елизавета Владимировна; Горячев, Владислав Сергеевич; Пархоменко, Алина Юрьевна (Гуманитарные исследования в Восточной Сибири и на Дальнем Востоке, 2024)
The article presents interpretations of the concept of justice at the theoretical level within various branches of humanities and in everyday consciousness. The authors describe the basic traditions of interpreting justice in ancient, medieval and modern European thought, as well as in Russian philosophy. The multi-layered theoretical understanding of justice is complemented by its interpretations in everyday consciousness, which are reconstructed on the basis of a survey of the representatives of three age groups.